2023
DOI: 10.1007/s40262-023-01228-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP2C19-Mediated Pharmacokinetic Drug Interaction of Tegoprazan, Compared with Vonoprazan or Esomeprazole

Abstract: Background and Objective CYP2C19-mediated drug interactions of acid-reducing agents are clinically important given the high possibility of concomitant administration with CYP2C19 substrates. This study aimed to evaluate the effect of tegoprazan on the pharmacokinetics (PK) of a CYP2C19 substrate, proguanil, compared with vonoprazan or esomeprazole. Methods A two-part, randomized, open-label, two-sequence, three-period crossover study was conducted in 16 healthy CYP2C19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Different from PPIs, P‐CABs were characterized by a rapid onset of action, a predictable antisecretory profile, and are not dependent on CYP2C19 genotype. Unlike esomeprazole and vonoprazan, pharmacokinetic studies have demonstrated that tegoprazan exhibits negligible CYP2C19 ‐mediated PK interactions, which may allow tegoprazan to be used concomitantly with CYP2C19 substrates [8]. In triple and bismuth‐containing quadruple therapies, PPI‐based regimens demonstrated similar efficacy to regimens on the basis of tegoprazan [9, 10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from PPIs, P‐CABs were characterized by a rapid onset of action, a predictable antisecretory profile, and are not dependent on CYP2C19 genotype. Unlike esomeprazole and vonoprazan, pharmacokinetic studies have demonstrated that tegoprazan exhibits negligible CYP2C19 ‐mediated PK interactions, which may allow tegoprazan to be used concomitantly with CYP2C19 substrates [8]. In triple and bismuth‐containing quadruple therapies, PPI‐based regimens demonstrated similar efficacy to regimens on the basis of tegoprazan [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Potassium‐competitive acid blockers (P‐CABs), represented by vonoprazan, have shown satisfactory efficacy in the eradication of H. pylori in dual therapy [7]. Tegoprazan, a novel type of P‐CABs, was shown to have comparable acid inhibitory capacity to vonoprazan by pharmacokinetics [8]. Its efficacy in eradicating H. pylori in bismuth‐containing quadruple therapy has been preliminarily demonstrated, but remains unelaborated in dual therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional inhibitors of the proton pump (PPIs), which need an acidic environment to be active, vonoprazan can inhibit acid secretion in both acidic and non-acidic conditions. 5 Vonoprazan has been demonstrated to raise gastric pH levels more effectively and for a longer duration than some conventional PPIs. It has also demonstrated efficacy in promoting the healing of gastric and duodenal ulcers, as well as in preventing nonsteroidal anti-inflammatory drug (NSAID)-induced gastroduodenal injury.…”
Section: Pharmacodynamics Of Vonoprazanmentioning
confidence: 99%